Selection of Suitable Binder in Solidification/Stabilization (S/S) Method: A Review - Murshid, Noorafizah; Mohd Kamil, Nor Amani Filzah (Penerbit UTHM, 2020)
One of the treatment that is gaining prominence to treat a variety of mixed organic and inorganic waste is solidification/stabilization (S/S) method. This treatment protects human health and the environment by immobilizing contaminants within the treated matrices and prevents migration of the contaminants. Thus, this chapter aims to recognize potential binders and others characteristic with satisfactory results besides reducing the remediation cost. This review will assist researchers in choosing suitable binders that are capable to improve the quality of treatment as well as contributing towards a sustainability remediation method. One of the criteria for a good binder is the pozzolan effect which can be determined based on chemical composition. Consequently, the present work recommended that if other materials have similar chemical composition with common binder, these materials may be suitable to use as binder in S/S method.